Back to the roots? Namíbia, Não!, de Aldri Anunciação - Henry Thorau (Universidade de Brasília, 2014)
This article analyzes how the “black comedy” Namíbia, Não!, by the young playwright Aldri Annunciation, from Bahia, elaborates the last consequences of the famous Brazilian racial democracy and of the human rights, and how it goes until the limits of the “politically correct” post-colonialist discourse in Brazil of the XXI century.